Crystal structure of 14-(R)-(2′-cyano-phenoxy)-3,19-diacetyl andrographolide, C31H37NO7 - Liu Zhuyun; Ding Pengfei; Yang Shanshan; Zhai Donghua; Sha Yunying; Zhang Ruifang; Wang Lizhong (Zeitschrift für Kristallographie - New Crystal Structures)
C31H37NO7, monoclinic, P21 (no. 4), a = 8.1269(1) Å, b = 11.0527(1) Å, c = 16.3586(2) Å, β = 97.973(1)°, V = 1455.19(3) Å3, Z = 2, Rgt (F) = 0.0467, wRref (F 2) = 0.1308, T = 293(2) K.